Generation of a Liver Orthotopic Human Uveal Melanoma Xenograft Platform in Immunodeficient Mice - Kageyama, Ken (J Vis Exp, 2019)
In recent decades, subcutaneously implanted patient-derived xenograft tumors or cultured human cell lines have been increasingly recognized as more representative models to study human cancers in immunodeficient mice than traditional established human cell lines in vitro. Recently, orthotopically implanted patient-derived tumor xenograft (PDX) models in mice have been developed to better replicate features of patient tumors. A liver orthotopic xenograft mouse model is expected to be a useful cancer research platform, providing insights into tumor biology and drug therapy. However, liver orthotopic tumor implantation is generally complicated. Here we describe our protocols for the orthotopic implantation of patient-derived liver-metastatic uveal melanoma tumors. We cultured human liver metastatic uveal melanoma cell lines into immunodeficient mice. The protocols can result in consistently high technical success rates using either a surgical orthotopic implantation technique with chunks of patient-derived uveal melanoma tumor or a needle injection technique with cultured human cell line. We also describe protocols for CT scanning to detect interior liver tumors and for re-implantation techniques using cryopreserved tumors to achieve re-engraftment. Together, these protocols provide a better platform for liver orthotopic tumor mouse models of liver metastatic uveal melanoma in translational research.